Student's Perception on the Use of Artificial Intelligence (AI) ChatGPT in English Language Learning: Benefits and Challenges in Higher Education - Roudlotun Nurul Laili; Wahyu Adri Wirawati; Muhammad Nashir (ITScience (Information Technology and Science), 2024)
English language learning in higher education has challenges, particularly for non-English majors such as health science students, due to lack of motivation and material. Incorporating AI in learning is becoming popular and of increasing interest, especially in language learning environments. The research examined students' attitudes toward using ChatGPT as a learning aid in English learning and its potential advantages and weaknesses. This study employed a descriptive qualitative approach. It used a questionnaire administered to 45 health science students who used ChatGPT in English and 10 purposively sampled students for semi-structured interviews to obtain more comprehensive data about their experiences. The findings reveal that the AI tool is valued for its ability to explain complex topics, expand vocabulary, and help with writing. However, the following challenges were noted: information overload, complete reliance on the AI system, and the need for personalized responses. These insights stress the necessity of harmonizing technology with conventional teaching techniques. The implications indicate that although AI tools like ChatGPT can support language learning, human interaction is also significant. Integrating ChatGPT in English learning can be a worthy addition that will help students engage more and yield many positive learning outcomes. However, educators must tackle issues related to overdependence on AI-generated content and its information quality.